ANALISIS PENDAPATAN USAHATANI KELAPA SAWIT PADA POLA MITRA DAN POLA SWADAYA DI KECAMATAN MARO SEBO ILIR KABUPATEN BATANGHARI - Anugrah Pratama, Rizki; Mara, Armen; Saputra, Ardhiyan (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2019)
This research aim to know the difference management of oil palm farming partner pattern and self-help pattern and analyze the income of oil palm farming with partner pattern and self-help pattern in District of Maro Sebo Ilir, Batanghari Regency. The selection was done deliberately with the consideration that the District of Maro Sebo Ilir is one of the areas of oil palm plantation which has the highest productivity in Batanghari Regency and has two pattern of palm oil farming. The sampling methodology using of simple random sampling method with respondent as many as 82 farmer’s consist of partner pattern as many as 42 farmer’s and self-help pattern as many as 40 farmer’s. Data analysis using the method two different test average method calculate by SPSS software. The results show that there is a difference between management of oil palm farming partner pattern and self-help pattern that caused by the existence of coaching and intensive control of the company, land productivity and fresh fruit bunch (FFB) quality that owned by partner pattern farmer’s are better than land productivity and fresh fruit bunch (FFB) quality that owned by self-help pattern farmer’s. The farmer’s income on the partner pattern is higher that self-help pattern income, where the average income of oil palm farming in research area for partner pattern is Rp. 29.873.936/Ha/Year and total cost is Rp. 16.589.355/Ha/Year. For oil palm farming self-help pattern, average income of palm oil farming is Rp. 22.456.318/Ha/Year and total cost is Rp. 15.028.142/Ha/Year. Key words : Income, Partnership, Oil Palm